The automatic hate [videorecording (DVD)] - Lerner, Justin, 1980-; Cross, Joseph, 1986-; Clemens, Adelaide, 1989-; Schiff, Richard, 1955- (Film Movement series, 2016)
When Davis Green's alluring young cousin Alexis appears on his doorstep one night, he discovers that a side of his family has been kept secret from him. Against his father's wishes, Davis travels to rural, upstate New York to meet his other cousins. While wrestling with a taboo attraction to one another, he and Alexis attempt to reunite their families, uncovering the reasons behind a long-standing rift and the shocking secret that tore their fathers apart.